Новосельский клад монет второй половины XVII века - Кожокару, В.М.; Кокоржицкая, Т.Н. (Материалы по археологии Северного Причерноморья, 2011)
In 2005 on the territory of village Novoselskoje (Odessa region) was discovered a hoard of silver coins of the XVII century. It consisted of 14 coins issued in Poland (1), Holland (6), France (6) and Lorraine (1), probably, including also coins of the Ottoman Empire.